2012
DOI: 10.1029/2012gl052712
|View full text |Cite
|
Sign up to set email alerts
|

Glacier volume‐area relation for high‐order mechanics and transient glacier states

Abstract: [1] Glacier volume is known for less than 0.1% of the world's glaciers, but this information is needed to quantify the impacts of glacier changes on global sea level and regional water resources. Observations indicate a power-law relation between glacier area and volume, with an exponent g ≈ 1.36. Through numerical simulations of 3D, high-order glacier mechanics, we demonstrate how different topographic and climatic settings, glacier flow dynamics, and the degree of disequilibrium with climate systematically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 22 publications
11
71
4
Order By: Relevance
“…However, differences larger than 10 % (20 %) are assessed for subsample sizes smaller than 80 (40) glaciers. These numbers are consistent to first order with the findings by Adhikari and Marshall (2012), who analyzed a synthetic set of glaciers and found that "ca. 200 glaciers are required to produce stable solution[s] of scaling parameters".…”
Section: Applications With Real-world Datasupporting
confidence: 79%
See 2 more Smart Citations
“…However, differences larger than 10 % (20 %) are assessed for subsample sizes smaller than 80 (40) glaciers. These numbers are consistent to first order with the findings by Adhikari and Marshall (2012), who analyzed a synthetic set of glaciers and found that "ca. 200 glaciers are required to produce stable solution[s] of scaling parameters".…”
Section: Applications With Real-world Datasupporting
confidence: 79%
“…This observation seems to contradict earlier findings that indicate time-varying parameters (e.g. Adhikari and Marshall, 2012), but can be explained by (a) the standard errors associated with the estimated parameters, which are mainly a function of the absolute number of (V, A)-pairs available for the estimate itself, and (b) the consistency of the estimated parameters for the two points in time, which is given when assuming constant parameters, but not when these are time-varying. For a population of 100 glaciers for instance, using 50 % of the sample for estimating the parameters would lead to (i) two subsamples of 50 (V, A)-pairs (one for t1 and one for t2), in the case of two different sets of parameters being estimated, or (ii) a subsample of 100 glaciers, if constant parameters were assumed.…”
Section: Accuracy Of Volume Changes Estimated From Changes In Areacontrasting
confidence: 56%
See 1 more Smart Citation
“…According to Meier and others (2007), estimated volume errors for individual glaciers could exceed 50% but these uncertainties are reduced to 25% for an ensemble of glaciers. Consistent with these results, a recent study by Adhikari and Marshall (2012), using a V-A relationship based on a sample of 280 synthetic random mountain glaciers, has shown that, when estimating the volumes for all individual glaciers in their ensemble, the average glacier volume error is small (2.8%), with a mean absolute error of 18.3%.…”
Section: Discussionsupporting
confidence: 66%
“…A minimum sample size of $100 glaciers is recommended (Bahr, 2012;Farinotti and Huss, 2013). Although more accurate scaling relations can be obtained through characterization of individual glacier shape, slope and size ( Adhikari and Marshall, 2012;Grinsted, 2013) and by local calibration, scaling approaches still have large uncertainties (Haeberli and Hoelzle, 1995;Cogley, 2012;Farinotti and Huss, 2013). Scaling does not, for instance, account for individual glacier characteristics such as surface geometry or local climate, and does not provide information on the spatial distribution of ice thickness.…”
Section: Introductionmentioning
confidence: 99%